Striving for Work-Life Balance at Entry Level Jobs: Challenges to Develop Professionalism in Bangladesh - Haque, Afdalin Bin; Ahmed, Aryana Anan (Asian Business Review, 2016)
The rising issue regarding the decline in organizational commitment of employees is nowadays a primary concern of employers and also HR department of any organization. These issues are observedin the entry level jobsmore densely where the socialization process takes place and in such area the newcomers feel deprived of any kind and every kind of facility. A fresh graduate joining into the workforce faces new challenges every day and mostly the Work-Life balance issue which is related to his or her job satisfaction and ultimately commitment towards his organization. The aim of this study is to identify the factors, especially the thoughts of employees regarding their Work-Life balance in an entry level job. The study will also bridge the gap between the expectation and realities of employees’ Work-Life balance and prescribing some corrections to the work structure. JEL Classification Code: J28; J29